Gradual Progress Through Diligent Study and Persistent Practice: On Enhancing the Writing Proficiency of English Majors - Na, Ma (Journal of Research in Vocational Education, 2025)
This paper explores effective strategies for improving the writing proficiency of English majors in higher education contexts. Drawing on pedagogical experience and student feedback, the study emphasizes a holistic, long-term approach grounded in vocabulary enrichment, extensive reading, and the development of English language thinking. It argues that sustainable improvement in writing cannot be achieved through short-term exam-oriented training but requires systematic and integrated efforts across multiple linguistic and cognitive domains. Practical implications for curriculum design and classroom instruction are discussed.